Optimization of Tunnel‐Junction for Perovskite/Tunnel Oxide Passivated Contact (TOPCon) Tandem Solar Cells. Issue 24 (23rd October 2021) - Shou, Chunhui; Zheng, Jingming; Han, Qingling; Zeng, Yuheng; Ding, Waner; He, Haiyan; Liao, Mingdun; Yang, Xi; Sheng, Jiang; Yan, Baojie; Ye, Jichun
Abstract : A systematic study of the formation of the tunnel‐junction for perovskite/TOPCon tandem solar cells is presented, which consists of a B‐doped poly‐Si (p + ‐poly‐Si) and P‐doped poly‐Si (n + ‐poly‐Si) double‐layer structure. The rear emitter double‐side TOPCon solar cell is selected as the bottom cell in tandem solar cells, where a p + ‐poly‐Si/SiO x forms the rear emitter and an n + ‐poly‐Si/SiO x forms the front field with the poly‐Si layer deposited by plasma‐enhanced vapor deposition (PECVD) and crystallized in a furnace. The tunnel‐junction is formed by depositing an additional B‐doped a‐Si:H (p + ‐a‐Si:H) on the front n + ‐poly‐Si and following a rapid thermal anneal (RTA) to partially crystallize the p + ‐a‐Si:H with minimized interdiffusion of B and P. The tunnel‐junction is systematically optimized and it is found that the RTA process at 700 °C produces the optimized tunnel‐junction with the minimal contact resistivity of ≈16 mΩ cm 2 . The tunnel‐junction formation affects the passivation of the front field TOPCon, but the losses in the passivation quality can be recovered by a forming gas annealing. This process provides a simple and useful method for making the tunnel‐junction in perovskite/TOPCon tandem solar cells. Abstract : An optimization of the tunnel‐junction for perovskite/TOPCon tandem solar cells is proposed, in which the rapid thermal anneal process is used to prevent the interdiffusion of B and P atoms and a minimal contact resistivity of ≈16 mΩ cm 2 at 700 °C is achieved. In addition, the passivation loss due to rapid thermal anneal can be recovered.